2007
DOI: 10.1007/s00417-007-0708-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results after transscleral diode laser cyclophotocoagulation in refractory posttraumatic glaucoma and glaucoma in aphakia

Abstract: TDLC is moderately effective in advanced posttraumatic glaucoma and glaucoma in aphakia, more effective in older than younger patients, not influenced by prior other glaucoma surgery, and despite a high re-treatment rate very safe in both groups of glaucoma. For younger patients with severe secondary glaucoma in particular, new treatment strategies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 20 publications
1
23
0
6
Order By: Relevance
“…This study comprised dark-skinned pigmented Asians of North India and the 58.5 % reduction in IOP attained was very similar to success rate of 59 % documented in a recent study done on the darker pigmented races of South India [17]. This would indicate that although the effectivity varies from 34 to 87 % between lighter pigmented Caucasian race and darker pigmented Asian race [16,[18][19][20], minor alterations in brown-skinned races do not translate into significant difference in the effect of laser on the ciliary epithelium.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This study comprised dark-skinned pigmented Asians of North India and the 58.5 % reduction in IOP attained was very similar to success rate of 59 % documented in a recent study done on the darker pigmented races of South India [17]. This would indicate that although the effectivity varies from 34 to 87 % between lighter pigmented Caucasian race and darker pigmented Asian race [16,[18][19][20], minor alterations in brown-skinned races do not translate into significant difference in the effect of laser on the ciliary epithelium.…”
Section: Discussionsupporting
confidence: 84%
“…The various disabling complications noted after DLCP in the literature [16,[19][20][21] namely phthisis, chronic hypotony, corneal graft decompensation, macular pucker, cystoid macular edema, vitreous hemorrhage, loss of visual acuity, retinal detachment, uveitis, malignant glaucoma [22], and corneal edema [23] did not occur in this series over the entire follow-up. The lower laser parameters used avoidance of horizontal 3 and 9 o'clock meridian could be a factor which accounted for no sight threatening or severe complications in this series.…”
Section: Discussionmentioning
confidence: 75%
“…Numerous publications have reported significant ocular hypotensive effects in various types of glaucoma using diode TSCPC; furthermore, fewer complications have been encountered compared to previous modalities 13-17. By and large, TSCPC has been studied as a treatment option for glaucoma refractory to medical and/or surgical means, but a small and growing number of investigations are giving promising results for TSCPC as a primary surgical method 18-20…”
Section: Introductionmentioning
confidence: 99%
“…Scholte et al reported that TDCP was less effective in younger patients with refractory glaucoma. 27 Our study showed no significant correlation between age and mean IOP reduction. The study also found a significant correlation between baseline IOP and mean IOP reduction.…”
Section: Discussionmentioning
confidence: 44%